Housing market and current account imbalances in the international economy - Maria Teresa Punzi (Bank of Finland, 2012)
This paper presents a two-sector, two-country model showing that inflation in the housing market, a low personal savings rate, and a construction investment boom can contribute to a large current account de cit. In the model, demand by a group of households in the domestic country is constrained by the availability of collateral. This implies more procyclical debt capacity because constrained households can borrow against the increase in the value of their houses during an expansion. A higher degree of financial liberalization and development helps constrained households reach higher loan-to-value ratios, thus relaxing their borrowing constraints. The resulting higher net worth and lower need for savings imply a worsening current account.
URN:NBN:fi:bof-20140807349
Keywords: 330